1943
DOI: 10.1111/j.1939-0025.1943.tb05996.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant rearing and problem behavior.

Abstract: HERE has been heated conflict between exponents of institutional care and T exponents of its young, maturing rival-foster home care. Some have even conceived of all institutional care as being inherently sadistic. They find it difficult to fancy an institution that is not regimented, ritualized and depriving. In contrast, there are others who are inclined to be doubtful of the completely virtuous character of foster homes. One speaker with the latter attitude remarked "I knew, too, that the supposed love of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1943
1943
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Children living in substandard orphanages also are markedly delayed in general behavioral development (e.g., Dennis & Najarian, 1957;Goldfarb, 1943;Hunt, Mohandessi, Ghodssi, & Akiyama, 1976;Kaler & Freeman, 1994;Kohen-Raz, 1968), and this was true for children in the orphanages in this study (St. Petersburg-USA Orphanage Research Team, 2005; see Chapter II). In contrast, young children reared in an orphanage that met standards of best practice developed Stanford-Binet IQs typical of the parent-reared population (Gavrin & Sacks, 1963).…”
Section: General Behavioral Developmentmentioning
confidence: 60%
“…Children living in substandard orphanages also are markedly delayed in general behavioral development (e.g., Dennis & Najarian, 1957;Goldfarb, 1943;Hunt, Mohandessi, Ghodssi, & Akiyama, 1976;Kaler & Freeman, 1994;Kohen-Raz, 1968), and this was true for children in the orphanages in this study (St. Petersburg-USA Orphanage Research Team, 2005; see Chapter II). In contrast, young children reared in an orphanage that met standards of best practice developed Stanford-Binet IQs typical of the parent-reared population (Gavrin & Sacks, 1963).…”
Section: General Behavioral Developmentmentioning
confidence: 60%
“…This is reflected in the institution children's greater tendency to aimless, unreflective behavior, to brief persistence and minimal ambition in the solution of prob~ lems, to their more frequent characterization by problem behavior involving hyperactivity, restlessness and inability to concentrate, and to their greater tendency to lose sight of and to violate prohibitions. At a younger age the institution children give more obvious evidence of uncontrolled response in the emotional and social areas (4). Aggressive reactions are more common and the children Downloaded by [New York University] at 11:09 06 July 2015 deprivation and neglect from early infancy, a personality such as that demonstrated by the institution children is likely to result.…”
Section: Conclusion and Theoretical Implicationsmentioning
confidence: 98%
“…In a previous study (4), a comparison was made of 40 children in foster homes, who had each spent about the first two or three years of their lives in an infant institution (institutional children) and 40 children whose total experience had been in foster homes (foster home children). It was clearly demonstrated that the children placed in foster homes after babyhood rearing in an institution evidenced greater frequency of problem behavior than did the children with continuous foster home experience.…”
Section: New York Association For Jewish Children Foster Home Bureau mentioning
confidence: 99%
“…Finally, attachment scholarship has its origins in issues raised by clinical studies in the 1940s (Goldfarb, 1943;Spitz, , 1946aSpitz, , 1946b) that revealed severe emotional disturbance among infants raised in group care nurseries, and African American infants formed a disproportionately large subgroup of the negatively affected subjects in some of those studies (63% of the severely disturbed, but only 37% of the total sample) (Spitz, 1946b, p. 318). …”
Section: Scarr's Views On Interventions Tomentioning
confidence: 96%